PO‘LAT YUZASIGA PLAZMA NITRIDINI TA’SIR ETTIRISH NATIJASIDA UNING ISHQALANISHGA BARDOSHLIGINI OSHIRISH VA PARAMETRLARINI ASOSLASH - Kengboyev, S.A. (SCIENCE and SOCIETY, 2025)
Plasma nitration (changing the surface layer of steel by nitriding) was considered in the article. The metallographic tests carried out revealed the presence or absence of a thin, porous and heterogeneous nitrogen layer, a core in its unsaturated state and a change in thermal parameters. When changing the nitriding parameters, the process of changing gases, time and temperature of nitriding was proposed. To obtain the optimal result of the ion nitriding process, it is necessary to adjust the parameters of gas flow, time, and temperature.